Khadin system of runoff farming for crop production - Goyal, R. K.; Singh, J. P.; Gaur, M. K. (Indian Farming, 2018)
The constructions of khadin played a major role in developing agriculture and producing food grains for sustenance of desert dwellers in western region of Indian arid zone. Cropping pattern and crop productivity in khadin greatly depends on status of ponding of runoff water. Its productivity can be improved by adopting optimum design of bund based on local topography, rainfall and diversification in cropping system along with trees and grasses. Planning crops/trees/grasses for different parts of khadin further reduces the risk of complete failure due to drought and ensures life support system to the farmers. The khadin system also help in recharge of groundwater in downstream. Such system of runoff farming is highly recommended for extremely low rainfall areas.